From Internship to Employment: The Role of Career Adaptability in Enhancing Students’ Work Readiness (Indonesian Journal of Digital Business, 2025)
College graduates often face challenges when entering the workforce, particularly in terms of their readiness for the job. This study aims to evaluate the impact of internship experiences on their work readiness and to examine the role of career adaptability as a mediating variable. The method used is a quantitative approach via a survey involving 120 students from the Faculty of Economics and Business at Padang State University who have completed an internship program, selected using purposive sampling with three selection criteria. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.1.8. The results of this study indicate that: (1) Internship experience has been shown to significantly improve work readiness; (2) In addition, internship experience also helps improve an individual’s ability to adapt to career developments; (3) A person’s level of work readiness is also influenced by how well they are able to adapt in their career; and (4) career adaptability partially mediates the relationship between internship experience and work readiness. This study reinforces Career Construction Theory (Savickas, 2013), which states that experiences in professional environments shape an individual’s psychosocial ability to adapt and be prepared to face changes in their career. Educational institutions are advised to strengthen their programs.